2022
DOI: 10.12821/ijispm100102
|View full text |Cite
|
Sign up to set email alerts
|

Changes to team autonomy in large-scale software development: a multiple case study of Scaled Agile Framework (SAFe) implementations

Abstract: Large-scale transformations of agile ways of working have received more attention in the industry in recent years. Some organizations have developed their own solutions for scaling, whereas many have chosen trademarked frameworks. In large-scale agile software development, many developers and development teams carry out work simultaneously. When autonomous teams need to coordinate toward a common goal, they must sacrifice some level of autonomy. Development, testing, and integrations need to be coordinated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…Moreover, there are numerous barriers and challenges that inhibit the realization of the agile benefits in an organizational context [10,25]. Especially in large-scale transformation projects, basic agile principles such as team autonomy are hard to maintain [26].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are numerous barriers and challenges that inhibit the realization of the agile benefits in an organizational context [10,25]. Especially in large-scale transformation projects, basic agile principles such as team autonomy are hard to maintain [26].…”
Section: Introductionmentioning
confidence: 99%
“…To ease tension between team autonomy and inter-team alignment, creating incentives for co-location can be beneficial. Enforcing company-wide rules, such as co-location on a set day, may threaten team autonomy in a large-scale agile organization [12]. Instead, incentives could be used to encourage co-location.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there are more uncertainty, complexity, and dependencies between projects and teams, and thus coordination especially becomes a challenge [6]. Furthermore, the high degree of complexity and dependencies across teams threatens team autonomy [12]. A recent longitudinal study exploring coordination mechanisms in large-scale agile revealed that these mechanisms evolve in response to external and internal change events and that implementing the appropriate coordination mechanisms can significantly enhance the organization's resilience [4].…”
Section: Introductionmentioning
confidence: 99%
“…49 The implementation of frameworks is not indifferent to team autonomy. 50 Conboy and Carroll warn that should an organizational transformation be based on formal frameworks, boards may be tempted by the counterproductive pursuit of compliance with a particular framework rather than the benefits brought by individual component practices. 51 On top of that, deliverables of highly regulated industries are subjected to various regulation schemes beyond typical national-level requirements, thereby leading to a disruption of the agile process referred to as ScrumBut or even the unfeasibility of adopting a given framework.…”
Section: Large-scale Agile Transformationsmentioning
confidence: 99%
“…For instance, Putta et al when scrutinizing the implementation of the SAFe framework within a large financial corporate body encountered a series of challenges, two of which could potentially derail any SAFe‐centered organizational transformation: (1) the management of traditional companies might be unwilling to embark on a path of a far‐reaching rebuild of their organizations; (2) yielding control over pools of resources each manager controls in order to form agile release trains is likely to face strong resistance of political nature 49 . The implementation of frameworks is not indifferent to team autonomy 50 . Conboy and Carroll warn that should an organizational transformation be based on formal frameworks, boards may be tempted by the counterproductive pursuit of compliance with a particular framework rather than the benefits brought by individual component practices 51 .…”
Section: Background and Related Workmentioning
confidence: 99%